Palinología de la Formación Monte Chico (Cretácico Tardío) de la Provincia de Santa Cruz, Argentina: Esporas - Povilauskas, Leticia Karina (Revista Brasileira de Paleontologia)
Diverse palynological assemblages composed by both continental and marine palynomorphs were recovered from the Monte Chico Formation, Late Cretaceous, Santa Cruz Province. In this contribution palynological assemblages were studied. The samples were taken from the all section of this unit. Fifty eight species of spores were herein identified. They belong to the genera: Baculatisporites, Biretisporites, Camarozonosporites, Ceratosporites, Cicatricosisporites, Clavifera, Concavissimisporites, Converrucosisporites, Cyathidites, Cyatheacidites, Deltoidospora, Dictyophyllidites, Foveosporites, Echinosporis, Gabonisporis, Gleicheniidites, Interulobites, Ischyosporites, Klukisporites, Kuylisporites, Laevigatosporites, Leiotriletes, Leptolepidites, Neoraistrickia, Ornamentifera, Peromonolites, Perotriletes, Polypodiidites, Punctatosporites, Reticuloidosporites, Retitriletes, Rouseisporites, Rugulatisporites, Stereisporites, Trilites, Trilobosporites, Tuberculatosporites and Verrucosisporites. On the basis of the stratigraphic distribution of the identified species, mainly in Argentina and Antarctica, joined with the presence of Camarozonosporites ohaiensis and Ischyosporites volkheimeri, a Maastrichtian age is here suggested. The palynological assemblages obtained would typically indicate a nearshore marine environment with more marginal conditions towards to the upper section. Foram recuperadas associações palinológicas de sedimentos provenientes da Formação Monte Chico, Cretáceo Superior, Província de Santa Cruz, constituídas por elementos marinhos (cistos de dinoflagelados) e continentais. As amostras pertencem à parte superior desta formação. Nesta contribuição foram estudados 58 espécies de esporos, pertencentes aos seguintes gêneros: Baculatisporites, Biretisporites, Camarozonosporites, Ceratosporites, Cicatricosisporites, Clavifera, Concavissimisporites, Converrucosisporites, Cyathidites, Cyatheacidites, Deltoidospora, Dictyophyllidites, Foveosporites, Echinosporis, Gabonisporis, Gleicheniidites, Interulobites, ...